Dampak E-commerce terhadap Perilaku Konsumen : Studi Perbandingan Studi Kasus Belanja Online dan Offline di Kabupaten Bima - Wanda Nurul Afriani; Asril Hermawan; Jasman Jasman (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study examines the impact of e-commerce on consumer behavior by comparing online and offline shopping patterns in Bima Regency. Using a mixed-method approach, the research analyzed data from 200 respondents through surveys and in-depth interviews. The findings reveal significant shifts in consumer behavior, with 65% of respondents showing increased preference for online shopping platforms. Key factors influencing this shift include convenience, price comparisons, and product variety. However, certain product categories still maintain strong offline shopping preferences. The study contributes to understanding local consumer behavior in the digital transformation era.